A global stability result for primal-dual congestion control algorithms with routing. - Voice, Thomas (Computer communication review.)
We prove a global stability result for a fluid approximation of a class of Internet-like communications networks operating a form of congestion control with routing. The network consists of an arbitrary interconnection of sources and links with negligible propagation delays. The model here allows for arbitrary strictly concave utility functions and the presence of dynamics at both sources and links.